Implementation of a web-based system to measure, monitor, and promote school engagement strategies. A Chilean experience - Saracostti, Mahia; de Toro, Ximena; Rossi, Andrea; Lara, Laura; Sotomayor, María Belen (Frontiers in Psychology, 2022)
This paper presents the implementation and usability of a technology-based web system and the available evidence on educational engagement's predictive capacity to influence students' educational trajectories in Chilean schools. The web-based system was developed through collaborative work between universities, the information technology team, school communities, and stakeholders (government institutions). It is an online system composed of six steps whose axis is centered on a decision-making space between teachers-students-parents (School Engagement Board) tasked with applying online and scientifically validated school engagement and contextual factors measurement instruments, checking specific report results for each actor involved in the system (teacher, School Engagement Board coordinator, school) as well as reviewing promotion strategies relevant to the school context and managing the implementation of strategies supported by the management datasheets that the model offers to schools. The objective of this paper is to present the usability of the system through a case study of the implementation in Chilean public schools. In order to discuss about what elements should be incorporated to adjust and improve the usability of the system and to guarantee its effective implementation, the paper describes those aspects that have favored and/or hindered the use of this educational technological platform in the Chilean case. The results show that there have been more difficulties related to management aspects than IT aspects, which indicates that these conditions are critical for implementation, even when SIESE is designed for stand-alone use. Although there are aspects to be improved, such as extending its use to other browsers, improving the intervention guidelines and other systems functionalities, this web-based system has been considered by the educational communities as a simple, useful, and intuitive platform. The paper concludes on the importance of having this type of platform in Chile and other Latin American countries, for its contribution to school management -being helpful for day-to-day educational practice- due to the different technical facilitators.